L'ensenyament bilingüe i els mètodes d'immersió - Strubell i Trueta, Miquel (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The author takes a close look at the definition and the typology of bilingualism and critically considers experiences of immersion in Catalonia.